Staying safe with healthy habits - Murray, Julie (Coronavirus (Abdo Kids), 2021)
This title explains what a virus is, what a coronavirus is, and how it spreads. The rest of the title is dedicated to explaining simple ways kids can stay healthy, like eating a nutrient-rich snack, getting lots of sleep, exercising by playing outside, and-of course-washing their hands!